Integrasi Nilai-Nilai Moderasi Beragama Persektif Al-Quran Melalui Penguatan Literasi Media - Fitriani, Fitriani (Universitas Islam Sultan Agung, 2021)
The purpose of this study is to discuss the integration of the values of religious moderation from the perspective of the Qur'an through strengthening media literacy. This research uses a qualitative approach through library research, namely research techniques using library research related to the theme or problem that is carried out. The results and discussion of this study indicate that the values of religious moderation in the perspective of QS Al-Baqarah (2): 143 include: Tawassuth, namely being a moderate person, not being extreme in religion, practicing religious teachings through the middle way by not reducing and also exaggerating -exaggerating, and not taking sides or tending to one party. Tawazun, namely being a human being who is able to carry out a balance of life in this world as well as in the hereafter. I'tidal, which is being a human being who is fair in various ways. Trying to be the best of human beings, namely by having good morals among others, helping each other, respecting each other, spreading kindness and justice, having noble character, not blaspheming and bringing each other down, not blaming each other, and not feeling the most right. The values of religious moderation from the perspective of the Qur'an must be well campaigned for the community, and integrated in daily life, therefore it is very important to strengthen media literacy with the aim that people are not easily provoked by radical-based groups. , extreme, conservative, and exclusive.